2021
DOI: 10.3390/app11188638
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical and Antibiotic Pollutant Levels in Wastewater and the Waters of the Zarqa River, Jordan

Abstract: Assamra wastewater treatment plant (WWTP) is the largest treatment facility in Jordan. Treated wastewater is discharged into the Zarqa River (ZR) and used to irrigate fodder and vegetables. ZR also includes surface runoff, stormwater, and raw wastewater illegally discharged into the river. This study examined pharmaceutically active compounds (PhAC) in water resources in the ZR basin. Samples of WWTP influent and effluent and river water from four sites along ZR were collected. Concentrations of 18 target anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…It treats wastewater released from the Zarqa River Basin. Moreover, the facility treats an average flow of 267,000 m 3 of wastewater, serving a population of 2.2 million living in the Amman and Zarqa areas [ 44 ]. King Abdullah Canal is Jordan’s most important source of drinking and agricultural water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It treats wastewater released from the Zarqa River Basin. Moreover, the facility treats an average flow of 267,000 m 3 of wastewater, serving a population of 2.2 million living in the Amman and Zarqa areas [ 44 ]. King Abdullah Canal is Jordan’s most important source of drinking and agricultural water.…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation for the low level of xenoestrogens in all samples is that the sample collections were conducted during the winter, which may dilute the xenoestrogens. In addition, degradation, evaporation, and adsorption are potential mechanisms contributing to lowering the activity of xenoestrogens [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the north coast of Java Island, paracetamol levels have been determined to be 610 ng L −1 [ 39 ]. A high concentration of paracetamol was found in the influent of the wastewater treatment plant, about 24,000 ng L −1 , and in the Zarqa River, about 600 ng L −1 [ 40 ]. There is also evidence of paracetamol in a drinking water treatment plant in Spain, with a concentration of 25.6 ng L −1 [ 41 ].…”
Section: Biotoxicity Of Pharmaceutical Active Compoundsmentioning
confidence: 99%
“…It has been reported that 90% of the pharmaceuticals are excreted in urine or feces after consumption and end up in wastewater. , Traditional wastewater treatment processes cannot completely remove these pharmaceuticals, which are thus released into downstream environments through wastewater streams . Currently, nonantibiotic pharmaceuticals have been detected in surface water, drinking water, aquaculture wastewater, and landfill leachate. Nonantibiotic pharmaceuticals can accumulate in large quantities in the environment due to their high persistence and low biodegradation rates . For example, five nonantibiotic pharmaceuticals were detected from the Baiyangdian Lake located in northern China, and the total concentration accounted for 53.3% of all detected pharmaceuticals, while antibiotics only accounted for 46.7% .…”
Section: Introductionmentioning
confidence: 99%